2012
DOI: 10.4172/2161-0991.s3-001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Myrtus Communis L. Extracts on Attenuation of Liver Normothermic Ischemia-Reperfusion Injury

Abstract: The Common Myrtle (Myrtus communis L.) is rich in antioxidants, particularly in anthocyanin. It was recognized for its anti-inflammatory and anti-thrombotic effects.The aim of our work is to evaluate the effect of Common Myrtle on a model of hepatic ischemia-reperfusion in Rat.Two morphs were chosen: white fruit Myrtle and black fruit Myrtle. Within each morph, fruit and leaf were separated and obtained extract were used to determine their effects on the hepatic model of ischemia-reperfusion.Our work was condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…To evaluate the effect of myrtle leaf and fruit extracts on ischemia‐reperfusion, the levels of transaminases and the concentration of monoethylglycinexylidide (for assessing the metabolic capacity of the liver) and MDA were determined after a single administration of 1 mg/kg lidocaine. Results showed that myrtle provided protection against the damage of ischemia‐reperfusion and this effect was variable, depending on the origin and type of myrtle's fruit (black or white) (Ferchichi et al ., ).…”
Section: Pharmacological Effectsmentioning
confidence: 99%
“…To evaluate the effect of myrtle leaf and fruit extracts on ischemia‐reperfusion, the levels of transaminases and the concentration of monoethylglycinexylidide (for assessing the metabolic capacity of the liver) and MDA were determined after a single administration of 1 mg/kg lidocaine. Results showed that myrtle provided protection against the damage of ischemia‐reperfusion and this effect was variable, depending on the origin and type of myrtle's fruit (black or white) (Ferchichi et al ., ).…”
Section: Pharmacological Effectsmentioning
confidence: 99%
“…The major polar constituents of Myrtus communis leaf extract are flavonoids and glycosides [20][21][22]. It is possible that the presence of flavonoids may be responsible for the observed antidiabetic activity [28].…”
Section: Discussionmentioning
confidence: 99%
“…Myrtle leaf extracts have been reported to possess antihyperglycemic and antibacterial properties. Recent reports have described antioxidant activities of different extracts of myrtle and certain ingredients, implying its potential as medicine for the treatment of diseases related to oxidative stress, including diabetes mellitus [20,21]. Myrtus communis L. (Myrtaceae) leaves and the volatile oil obtained from the leaves may impact blood glucose through different mechanisms some of which may influence insulin's activity [22].…”
mentioning
confidence: 99%
“…Liver ischemia/reperfusion injury represents the main complication of hepatic trauma, resection, or transplantation. The anti‐ischemic activities of myrtle have been demonstrated in a rat hepatic model of ischemia‐reperfusion, where berry and leaves extracts (25 mg/kg for 15 min before reperfusion) protected against ischemia, reducing the hepatic levels of MDA and transaminase activities (alanine and aspartate transaminase), as well as improving liver metabolic function (Ferchichi et al., 2011; Salouage et al., 2010).…”
Section: Effects On Human Healthmentioning
confidence: 99%